Diminishing returns: Nudging Covid-19 prevention among Colombian young adults - Allen Blackman; Bridget Hoffmann (Inter-American Development Bank (IDB), 2021)
Until a vaccine is widely available, face masks and other nonpharmaceutical interventions (NPIs) will continue to be the frontline defense against Covid-19 in developing countries. But their effectiveness depends critically on compliance by young adults, who are most likely both to become infected and to infect others. We conducted a randomized controlled trial in Bogotá, Colombia, to assess the effectiveness of informational nudges on university students concern about Covid-19, recent compliance with NPI recommendations, and intended future compliance. Although nudges boosted concern, they had limited effects on either recent or intended future compliance. We attribute these null results to high baseline levels of information about and compliance with NPIs an informational diminishing returns scenario that is likely to be increasingly common globally. Nudges were more effective at boosting recent compliance among participants who were politically left-wing, were relatively poor, and lived with more people.
Keywords: D8; D83; I1; I15; I18; O1; 330; behavioral economics; coronavirus; framing; health behavior; nonpharmaceutical intervention; randomized controlled trial